Aestheticism and Symbolism in the Tales of Oscar Wilde - Drahota-Szabó Barbara (2002)
In my thesis, I am going to analyse the Tales of Oscar Wilde in two ways. I chose this author because, first of all, in England in the late l9thcentury he was the most significant forerunner of the aesthetic movement whose motto was "art for art's sake". He could create a connection between Beauty and Art, and he also represented the marks of Aestheticism in his tales. When he wrote these Fairy Tales - which were published forbothchildren and adults, and consisted of nine short stories - he also considered the typical features of folk tales. Each tale can be esteemed as conventional fairy tales, both in their subjects and structures, carrying all the cultural and literary characteristics, includingthearchetypal symbolism as well, which is common in folk tales. In my first analysis, I try to prove Wilde's relationship with Love and Misery and I will emphasize the aesthetic marks, which are in connection with the seeking of Beauty in his nine tales. On the other hand, I can present how Wilde can apply the system of archetypal symbols in order to express the most important aesthetic aspects and how he is able todemonstrate the sharp contrast between differing social classes. I will illustrate the main symbols with some exact quotations in charts. Accordingly, my thesis statement is the following: Oscar Wilde can reflect the aesthetic aspects through the world ofhistales with the help of symbolism of the folk tales.